Characterization of a single‐isomer carboxymethyl‐beta‐cyclodextrin in chiral capillary electrophoresis. Issue 15 (15th May 2017) - Fejős, Ida; Varga, Erzsébet; Benkovics, Gábor; Malanga, Milo; Sohajda, Tamás; Szemán, Julianna; Béni, Szabolcs
Abstract : In this work, the synthesis, characterization, and chiral capillary electrophoretic study of heptakis‐(2, 3‐di‐ O ‐methyl‐6‐ O ‐carboxymethyl)‐β‐CD (HDMCM), a single‐isomer carboxymethylated CD, are presented. The pH‐dependent and selector concentration‐dependent enantiorecognition properties of HDMCM were investigated and discussed herein. The enantioseparation was assessed applying a structurally diverse set of noncharged, basic, and zwitterionic racemates. The increase in the selector concentration and gross negative charge of HDMCM improved the enantioseparation that could be observed in the majority of the cases. HDMCM was also successfully applied as BGE additive in NACE using a methanol‐based system in order to prove the separation selectivity features and to highlight the broad applicability of HDMCM. Over 25 racemates showed partial or baseline separation with HDMCM under the conditions investigated, among which optimal enantiomer migration order was found for the four stereoisomers of tadalafil, tapentadol, and dapoxetine, offering the possibility of a chiral CE method development for chiral purity profiling of these drugs.